Peranan Badan Pendapatan Daerah Kabupaten Kutai Kartanefara Dalam Meningkatan Pendapatan Asli Daerah Bersumber Dari Pajak Sarang Burung Walet (Di Tinjau Dari Peraturan Daerah Kabupaten Kutai Kartanegara Nomor 2 Tahun 2011 Tentang Pajak Daerah) - Megawati Hairuni; Wahyuni Safitri (Yuriska: Jurnal Ilmiah Hukum, 2019)
Kutai Kartanegara Regency as an autonomous region has regional development planning documents as an integral part of the provincial and national development planning systems. The greater role of Regional Original Revenue (PAD) means less regional dependence on central assistance. The purpose of this study was to determine the role of the Regional Revenue Agency of Kutai Kartanegara Regency in carrying out levies and carry out supervision of swallow nest owners in exercising their authority to pay taxes to increase local revenues and to determine the calculation of the swallow's nest tax rate which was set at 10% based on the Regulation Regency of Kutai Kartanegara Number 2 Year 2011 regarding Regional Tax. The method used in this study is normative with the main informant namely the Regional Revenue Agency of Kutai Kartanegara Regency. The results showed that the Regional Revenue Agency of Kutai Kartanegara Regency in carrying out levies and carrying out supervision of swallow bird nest owners in carrying out their authority to pay taxes to increase local revenue is still not optimal. Supervision should also be carried out in the implementation of levies, in order to evaluate the administration of levies. The calculation of the tax rate for swallow's nest which is set at 10% based on the Kutai Kartanegara Regency Local Regulation Number 2 of 2011 concerning Regional Taxes is good enough but in terms of implementation it must be carried out to the entrepreneur of swallow's nest.